Pengaruh Electronic Word of Mouth dan Kualitas Produk Terhadap Repurchase Intentions Konsumen Pada Produk Kopi Keliling Merek Segelas Pada Mahasiswa Universitas Sumatera Utara - Ramanda, Bima; Narwastu Sianturi, Isabel; Syafitri Lubis, Putri Nur; Tampubolon, Claudia Yonika; Hutajulu, Johansen (PT. Alahyan Publisher Sukabumi, 2024)
In the digital era, consumer decisions are increasingly influenced by online information, including Electronic Word of Mouth (E-WOM). At the same time, product quality remains a key factor in determining customer satisfaction and loyalty. This study analyzes how E-WOM and product quality affect repurchase intentions for Segelas mobile coffee products, particularly among students at the University of North Sumatera. Using a quantitative explanatory approach with 100 respondents, the study found that product quality significantly enchances repurchase intentions, while E-WOM has a smaller and statistically insignificant effect. These findings highlight the importance of product quality in encouraging repeat purchases. The study suggests that business owners focus on improving product quality to retain customers.